Isoflavone biomarkers are inversely associated with atherosclerosis progression in adults: a prospective study. Issue 1 (11th March 2021) - Zuo, Luo-Shi-Yuan; Tang, Xin-Yi; Xiong, Feng; Liu, Yu-Ping; Liu, Meng; Ling, Chu-Wen; Sun, Ting-Yu; Ling, Wenhua; Zhang, Zhe-Qing; Chen, Yu-Ming
ABSTRACT: Background: Many studies have examined associations between dietary isoflavones and atherosclerosis, but few used objective biomarkers. Objectives: We examined the associations of isoflavone biomarkers (primary analyses) and equol production (secondary analyses) with the progression of carotid intima–media thickness (cIMT), and whether inflammation, systolic blood pressure (SBP), blood lipids, and sex hormone–binding globulin (SHBG) mediated these associations, in Chinese adults. Methods: This 8.8-y prospective study included 2572 subjects (40–75 y old) from the GNHS (Guangzhou Nutrition and Health Study; 2008–2019). The concentrations of daidzein, genistein, and equol were assayed by an HPLC-tandem MS in serum ( n  = 2572) at baseline and in urine ( n  = 2220) at 3-y intervals. The cIMT of the common carotid artery (CCA) and bifurcation segment were measured by B-mode ultrasound every 3 y, and the progressions of cIMT ( ∆ cIMT) were estimated using the regression method. Results: Multivariable linear mixed-effects models (LMEMs) and ANCOVA revealed that subjects with higher serum isoflavones tended to have lower increases of CCA-cIMT. The mean ± SEM differences in 8.8-y ∆ CCA-cIMT between extreme tertiles of serum isoflavones were −17.1 ± 8.4, −20.6 ± 8.3, and −23.3 ± 10.4 μm for daidzein, total isoflavone, and equol ( P -trends < 0.05), respectively. LMEMs showed that the estimated yearly changes (95% CIs) (μm/y) in CCA-IMT were −2.0 (−3.8, −0.3), −1.9 (−3.6, −0.1), and −2.1 (−3.8, −0.3) in the highest (compared with the lowest) tertile of daidzein, genistein, and total isoflavones, respectively ( P -interaction < 0.05). Path analyses indicated that the serum equol–atherosclerosis association was mediated by increased SHBG and decreased SBP. Similar beneficial associations were observed in the secondary analyses. Conclusions: Serum isoflavones and equol exposure were associated with reduced cIMT progression, mediated by SHBG and SBP.